Transient and Dynamic Analysis of a Line-Start Radial Synchronous Reluctance Motor with Auxiliary Capacitive Winding - MUTEBA, MBIKA (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2023)
This paper deals with transient and dynamic analysis of a line-start radial synchronous reluctance motor (LSR-SynRM) with auxiliary stator capacitive winding (ASCW) suitable for direct drive industrial loads such as conveyor belts and centrifugal pumps. The machine which has been designed from an IE2-132S4 conventional foot mounted three-phase induction motor NEMA frame is modelled using Finite Element Method (FEM), then prototyped and tested for transient and dynamic capabilities. The stator slots house both main and auxiliary windings. The rotor laminations have two flux barriers, two radial magnetic ribs and four tangential magnetic bridges per pole. The upper and lower flux barriers accommodate copper bars, which are short circuited by common end rings. The time step Finite Element Model (FEM) coupled to an external capacitive circuit is utilized to analyze the transient behavior of LSR-SynRM. To validate the numerical method, a testbed is set up for experimental measurements. The measured results evidenced that for any given capacitance value connected to auxiliary winding, the LSR-SynRM successful pulled into synchronism when started with no-load and with light load up to 25% of the full load. The results further proved that the LSR-SynRM with ASCW may be started at no-load or light load, and successfully be fully loaded after it has reached the synchronous speed and still be able to meet the efficiency IE4, and while operating with excellent power factor